Beyond the Program: Understanding Mechanisms Through Which Nongovernmental Organizations Advance Equity in Stroke Care - Michelle L. A. Nelson (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Health disparities in stroke disproportionately affect marginalized and disadvantaged communities. This review examines the role of nongovernmental organizations (NGOs) in addressing disparities through a mechanism‐focused analytical framework rather than cataloging specific interventions. A thematic literature analysis identified 5 mechanisms by which NGOs contribute to health equity: community engagement and empowerment, place‐based service delivery and inclusive cultural adaptation, intersectoral partnership and coalition building, policy advocacy and systems change, and research engagement and knowledge translation. By examining mechanisms, this review offers a deeper understanding of how NGOs contribute to health equity. NGOs' contributions to addressing disparities may stem from their capacity to activate multiple mechanisms simultaneously. Being embedded within the communities they serve can help develop responsive interventions addressing social determinants of health that traditional medical models often overlook. NGOs leverage relationships through clinical–community partnerships and community coalitions to improve experiences and outcomes for underrepresented populations. Despite their potential, NGOS face substantial challenges that affect all mechanisms, including limited visibility within formal systems, precarious funding models, policy and regulatory barriers that misalign with community‐centered approaches, and operational constraints. These challenges reflect broader tensions between health care structures and the flexible, context‐sensitive approaches needed to address complex health disparities. This mechanism‐focused analysis suggests health systems should reconceptualize engagement with NGOs, not as a supplement to formal care but as a partner uniquely positioned to develop and deploy equity‐enhancing interventions. Health care systems can create more effective and sustainable approaches to addressing health disparities by supporting these fundamental mechanisms rather than replicating individual programs.